A STUDY OF FAMILY ENVIRONMENT AND EMOTIONAL INTELLIGENCE IN SECONDARY LEVEL STUDENTS - B. K. Gupta; Maurya, Nandan (International Journal of Research -GRANTHAALAYAH, 2025)
The objective of this study was to study the family environment and emotional intelligence of secondary level students. A survey method was used for this study. A sample of 100 secondary level students from Ambedkar Nagar district, Uttar Pradesh was selected. The present study concluded that there is no significant difference between the family environment and emotional intelligence of secondary level students.